Draft Fourth Five Year Plan 1969-74 Goa, Daman and Diu - Planning Commission (Planning Commission, 1969)
Goa, Daman and Diu were constituted as a separate Union Territory in 1962, after their liberation from Portuguese rule on December. 19. 1961. The Territory comprises three land blocks on the West Coast separated from each other by a distance of over 300 miles. Administratively also, the Territory is divided into three districts, respectively named Goa, Daman and Diu. The boundaries of Goa district are defined, in the north- by the Terekhol river which separates it from Maharashtra, in the east and south by Mysore State and in the west by the Arabian Sea.
Goa, Daman and Diu